1995
DOI: 10.1007/bf00860924
|View full text |Cite
|
Sign up to set email alerts
|

Growth, development and nutritional status in Japanese children under 2 years on continuous ambulatory peritoneal dialysis

Abstract: We examined the growth, development and nutritional status over a period of 10 years of 15 young children (< 2 years old) on continuous ambulatory peritoneal dialysis (CAPD). There were 6 males and 9 females with a mean age of 12.5 months, mean weight of 6.3 kg, mean height of 66.2 cm at the start of CAPD and a mean duration of therapy of 2.6 years. Height, weight, head circumference, development quotient (DQ), blood chemistry and dietary intake were assessed over a period of 10 years. The patients' mean heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…The data from our center extend the recently reported experience of Honda [12] that good growth and development can be attained with dialysis in infants and young children. His study followed 15 patients who started CAPD before the age of 2 years for up to 10 years.…”
Section: Discussionsupporting
confidence: 78%
“…The data from our center extend the recently reported experience of Honda [12] that good growth and development can be attained with dialysis in infants and young children. His study followed 15 patients who started CAPD before the age of 2 years for up to 10 years.…”
Section: Discussionsupporting
confidence: 78%
“…Some, but not all, reports have been able to establish a relationship between nutritional intake and growth. Growth velocity correlated positively with energy intake in 17 children with CRF [75], and with energy but not protein intake in 15 children on CAPD [76]. Growth velocity was inversely correlated with dietary protein intake and positively correlated with caloric intake both before the initiation of rhGH therapy and after the first year of treatment in 31 children on dialysis [77].…”
Section: Evidence For the Benefit Of Dietetic Input Dietary Supplemementioning
confidence: 99%
“…Geary and Haka-Ikse reported developmental delay in 41% of their infants with end-stage renal failure (ESRF) [2]. Later, Honda et al observed abnormal development at the end of PD in 69% of their Japanese patients <2 years of age at PD initiation [3]. Warady et al, on the other hand, detected neurodevelopmental delay in only 21% of their children undergoing PD treatment during infancy.…”
Section: Introductionmentioning
confidence: 95%